Anti‐glycoprotein 2 (anti‐GP2) IgA and anti‐neutrophil cytoplasmic antibodies to serine proteinase 3 (PR3‐ANCA): antibodies to predict severe disease, poor survival and cholangiocarcinoma in primary sclerosing cholangitis. Issue 2 (7th November 2020) - Wunsch, Ewa; Norman, Gary L.; Milkiewicz, Malgorzata; Krawczyk, Marcin; Bentow, Chelsea; Shums, Zakera; Mahler, Michael; Lopens, Steffi; Reinhold, Dirk; Franke, Andre; Schramm, Christoph; Roggenbuck, Dirk; et al.
Summary: Background: Primary sclerosing cholangitis (PSC) is associated with progressive liver disease and cholangiocarcinoma. Although risk stratification is crucial for making clinical decisions, it is hindered by a scarcity of proven prognostic markers. Aims: To assess the value of novel anti‐glycoprotein 2 (anti‐GP2) and anti‐neutrophil cytoplasmic antibodies to serine proteinase 3 (PR3‐ANCA) in combination with PSC‐specific clinical and laboratory markers as predictors of quality of life, disease severity, and cholangiocarcinoma in two large, independent cohorts of PSC patients Methods: Discovery (338 Polish patients) and validation (178 German patients) cohorts with PSC were evaluated. Anti‐GP2 (isoforms 1/4) was detected by ELISAs and PR3‐ANCA by chemiluminescence immunoassay. Clinical and laboratory data were collected and analysed. The outcome was defined as liver transplantation‐free survival and occurrence of cholangiocarcinoma during follow‐up. Results: In the discovery group, anti‐GP21/4 IgA and PR3‐ANCA were associated with liver dysfunction, anti‐GP21/4 IgA with risk scores for PSC and anti‐GP24 IgA with cirrhosis. All cholangiocarcinoma patients were positive for PR3‐ANCA and/or anti‐GP24 IgA. The association between anti‐GP2 IgA and liver biochemistry, risk scores, cirrhosis, impaired survival, and cholangiocarcinoma was confirmed in the validation cohort. Cox proportional‐hazards regression indicated anti‐GP21 IgA as an independent variable of poor outcome in both study cohorts. Analysis of the combined data showed that anti‐GP24 IgA and PR3‐ANCA were independent predictors for cholangiocarcinoma, while anti‐GP21 IgA and PR3‐ANCA were indicators for poor survival. Conclusions: Anti‐GP2 and PR3‐ANCA are prognostic antibodies in PSC as they identify patients at risk of severe disease, poor survival and biliary cancer.